IMPLEMENTASI KEBIJAKAN PELIMPAHAN WEWENANG DARI BUPATI KEPADA CAMAT DI KECAMATAN TANJUNGSARI KABUPATEN SUMEDANG PROVINSI JAWA BARAT - Isman Hadijaya (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2018)
ABSTRACT This study analyzes and obtain a description of Policy Implementation delegation of some authority of government of the Regent to the District Head in District Tanjungsari of Sumedang Regency. Design used in this study using descriptive research design with a qualitative approach. Data analysis techniques employed in descriptive research through data selection, data reduction, data presentation, drawing conclusions and verification. The results of this study can be revealed that the implementation of the policy of delegation of some powers to the District Head in District Regents Tanjungsari accordance with decree No. 55 of 2009 which bestows 22 (twenty two) areas of authority, are still not followed up with a technical guide its implementation, making it difficult for field implementation fully implemented and still can not run optimally. The obstacles faced by the integrated services that have not been implemented, in the sense of the service process in the district Tanjungsari not through one door and go through the procedure on each part in accordance with their main duty, so that the bureaucracy getting longer, there are still overlapping authority with Technical service or other agencies, so that the implementation of the service becomes not optimal, uniform pattern of delegation of authority to all the districts to make the pattern of service be the same and there is no specification tailored to the needs of local communities, Lack of Human Resources (HR). So that the delegation of authority is on target and in accordance with the needs, competencies and skills Increasing Human Resources (personnel) in the district Tanjungsari who will carry out the delegation of authority, the provision of funding support for the implementation of the delegation of authority from the Regents to the District Head in District Tanjungsari of Sumedang Regency in a way inventory and forecast demand infrastructure and facilities and where possible existing infrastructure be utilized in the process of implementation of the delegation of authority. Keywords: implementation, policy, authority delegation.